2019
DOI: 10.1002/prot.25819
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy of contact predictions in CASP13

Abstract: The accuracy of sequence‐based tertiary contact predictions was assessed in a blind prediction experiment at the CASP13 meeting. After 4 years of significant improvements in prediction accuracy, another dramatic advance has taken place since CASP12 was held 2 years ago. The precision of predicting the top L/5 contacts in the free modeling category, where L is the corresponding length of the protein in residues, has exceeded 70%. As a comparison, the best‐performing group at CASP12 with a 47% precision would ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 75 publications
2
86
0
Order By: Relevance
“…Previous studies have shown that long-range contacts, i.e. pairs separated by at least 23 residues in the sequence, are the most informative pairs for accurate reconstruction [24,25]. Hence, we designed our evaluation metrics focusing on long-range distances (see Figure 2).…”
Section: Evaluation Of Predicted Distance Mapsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that long-range contacts, i.e. pairs separated by at least 23 residues in the sequence, are the most informative pairs for accurate reconstruction [24,25]. Hence, we designed our evaluation metrics focusing on long-range distances (see Figure 2).…”
Section: Evaluation Of Predicted Distance Mapsmentioning
confidence: 99%
“…In a recent work [26] the Cheng group have reported that selecting or evaluating top L/x contacts does not work well for all proteins. Also, in the most recent CASP competition, the accessors of the contact prediction category have discussed many reasons for considering to evaluate top NC contacts instead of fewer contacts [25]. Although the P N C metric is not discussed for most contact prediction method papers, we believe that as more and more accurate contact prediction methods are being developed, this will emerge as a more informative and reliable metric.…”
Section: Evaluation Of Predicted Distance Mapsmentioning
confidence: 99%
See 2 more Smart Citations
“…Convolutional neural networks are a type of deep-learning model commonly used in computer vision applications. They have recently proven to perform well in residue contact prediction (Kandathil et al, 2019a;Schaarschmidt et al, 2018;Shrestha et al, 2019;Wang et al, 2018) and protein tertiary structure prediction (Greener et al, 2019;Kandathil et al, 2019b;Xu, 2019;Xu and Wang, 2019). We selected CNNs for protein structure-based ∆∆G prediction because we formulated this problem as a computer vision problem by treating protein structures as if they were 3D images.…”
Section: Model Architecturementioning
confidence: 99%